Reynolds Horizontal and Vertical Test Bench from an Educational Point of View - Abderrahmane Khechekhouche; Mokhtar Ghodbane; Imad Kemerchou; Ali Sadoun (Indonesian Journal of Educational Research and Technology, 2021)
The Reynolds Number Test Bench is a self-contained device that uses water to allow students to study laminar, turbulent flow regimes, and transition conditions. The vertical test bench does not allow a large number of students to see the experiment clearly, it only takes two people in front of the device to block the view of the rest of the students and this causes a problem. The idea of this work is to build a horizontal test bed that allows students to see the experience clearly and easily. The results obtained from our horizontal device are the same as that of the vertical bench.